2015
DOI: 10.1002/hed.23899
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of the physical therapy modalities applied in head and neck l ymphedema treatment

Abstract: The physical therapy modalities based on strategic manual lymphatic drainage, shoulder girdle massage, facial, tongue and neck exercises, compressive therapy at home, and patient education showed reduction of the lymphedema and pain, both of them secondary to head and neck cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 21 publications
0
36
0
3
Order By: Relevance
“…Para analisar as características clínicas e sociodemográficas dos pacientes atendidos no ambulatório de fisioterapia, foi delimitado metodologicamente o estudo do tipo retrospectivo, considerado desenho de estudo ideal para compreender e analisar os fatores de exposição pré-vios 7,10 , ou seja, ideal para conhecer o perfil dos pacientes que foram atendidos no ambulatório. Estudos retrospectivos são essenciais para delimitar diretrizes para que outros tipos de estudos sejam desenvolvidos, como os estudos do tipo ensaio controlado e os estudos prospectivos 10 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Para analisar as características clínicas e sociodemográficas dos pacientes atendidos no ambulatório de fisioterapia, foi delimitado metodologicamente o estudo do tipo retrospectivo, considerado desenho de estudo ideal para compreender e analisar os fatores de exposição pré-vios 7,10 , ou seja, ideal para conhecer o perfil dos pacientes que foram atendidos no ambulatório. Estudos retrospectivos são essenciais para delimitar diretrizes para que outros tipos de estudos sejam desenvolvidos, como os estudos do tipo ensaio controlado e os estudos prospectivos 10 .…”
Section: Discussionunclassified
“…Estudos retrospectivos são essenciais para delimitar diretrizes para que outros tipos de estudos sejam desenvolvidos, como os estudos do tipo ensaio controlado e os estudos prospectivos 10 . No entanto, a metodologia de coleta retrospectiva dos dados por revisão dos prontuários pode trazer alguns vieses, uma vez que alguns prontuários foram excluídos por falta de informações 7,10 . Da mesma maneira, Tacani, et al 7 coletaram informações de 32 prontuários de pacientes com diagnóstico de câncer de cabeça e pescoço, em São Paulo-SP, Brasil, sendo que 23% (n = 6) teve de ser excluído por dados incompletos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Some previous reports showed that physical therapy has efectiveness in head and neck cancer patients [60,61]. When patients have paralysis of the accessory nerve, physical therapists perform exercises for the trapezius muscle to reduce its dysfunction [62].…”
Section: Physical Therapymentioning
confidence: 99%
“…Patients with HNL may experience a wide range of physical, functional and psychological symptoms. Patients have been shown to encounter altered sensation within the head and neck region causing tightness, heaviness and hardness of the skin (Deng, Ridner, Murphy, & Dietrich, ; Deng et al., ; McGarvey et al., ); reduced range of movement in the neck (Deng, Murphy et al., ; Deng et al., , ; McGarvey et al., ; Tacani, ); difficulties with breathing (Bruns et al., ; Deng et al., ; Micke et al., ; Murphy & Ridner, ); trismus; and blurred vision (Deng, Ridner, Murphy et al., ; Deng et al., ). Patients who experience HNL are also known to experience negative effects on quality of life, body image and reduced socialisation (Brake et al., ; Bruns et al., ; Deng, Murphy et al., ; Deng, Ridner, Murphy et al., ; McGarvey et al., ; Micke et al., ; Smith et al., ).…”
Section: Introductionmentioning
confidence: 99%